Gestión estratégica y su incidencia en la productividad en la empresa embutidos la Madrileña de la ciudad de Latacunga. - Pastuña Jacome, Myrian Alexandra (2023)
The general objective of this research project is to design a strategic management model for the company Embutidos the Madrileña in the city of Latacunga. For this study, a mixed approach was used, bibliographical-documentary and field research. As a technique, the survey and the questionnaire is the instrument with which it was possible to collect information from the manager and the workers regarding strategic management and productivity. To determine the incidence of strategic management, two hypotheses were formulated, the SPSS software was used, the results support the alternative hypothesis (H1) that affirms that strategic management affects the productivity of the company, the findings show a positive correlation of ( r = 0.855) between both variables. The proposed structure of the strategic management model consists of three stages: the first formulation of the strategy, the second implementation of the strategy and the last stage of control and monitoring. In the first stage, the vision and mission were first developed, then an internal and external analysis of the company's environment (FODA) was carried out based on this information, long-term strategic objectives and strategies were established. In the second stage, the necessary policies and allocation of resources were established, and finally, in the last stage of control and monitoring, the strategic map was drawn up and subsequently the Balanced Scorecard was prepared. Therefore, the company "Embutidos La Madrileña" will greatly benefit from the implementation of this strategic management model, since it will contribute to the growth, productivity and competitiveness of the company in the sausage market.